Employer's information and promotion-seeking activities - Gil S. Epstein (Institute for the Study of Labor (IZA), 2012)
This paper presents a model in which promotion of employees within the internal firm hierarchy is determined by the individuals' allocation of time between promotion/rent-seeking and productive activity. We consider the effect of an increase in the employer's knowledge (information) regarding the employees' productivity levels on the total time spent by the workers in non-productive promotion-seeking activities.
Keywords: D2; D72; J2; 330; promotion-seeking activities; contest; knowledge; Karriereplanung; Rent Seeking; Arbeitskräfte; Zeitverwendung; Arbeitsproduktivität; Unternehmer; Information; Theorie